Survey Deficiencies as Quality Indicators in Oregon Assisted Living Communities. (4th December 2021) - Tunalilar, Ozcan; Lin, Sunny; Carder, Paula
Abstract: Background and Objectives: License inspection data have commonly been used as a quality measure for nursing homes but have not yet been used to assess the quality of assisted living/residential care (AL/RC) communities. Drawing on resource dependency theory, we test the hypothesis that structural and environmental characteristics influence AL/RC quality as measured by deficiency citations ("deficiencies") issued during license inspections. Research Design and Methods: Using data from 526 licensed AL/RC communities in Oregon that received a license inspection visit between 2008 and 2016, we examined the prevalence of deficiencies by type and year. We estimated regression models to identify structural and environmental characteristics associated with the number of deficiencies. Results: Most (79%) inspections resulted in at least one deficiency. The most common deficiencies concerned medications and treatments (57%), change of condition and monitoring (48%), and resident health services (45%). Structural characteristics associated with higher odds of receiving one or more deficiencies included larger size, memory care designation, shorter administrative tenure, and for-profit status. Environmental characteristics associated with higher odds of receiving one or more deficiencies included rural location, lower unemployment, and market concentration. The number and likelihood of a given community receiving a deficiency decreased over time. Discussion and Implications: Resource dependency theory constitutes a useful framework to consider the role of structural and environmental factors that affect AL/RC quality, including resident needs, institutional knowledge, resource availability, and market pressure. License inspection data are a viable option for assessing the quality of AL/RC communities.